2021
DOI: 10.1186/s12943-021-01417-4
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs’ cap-independent translation protein and its roles in carcinomas

Abstract: Circular RNAs a kind of covalently closed RNA and widely expressed in eukaryotes. CircRNAs are involved in a variety of physiological and pathological processes, but their regulatory mechanisms are not fully understood. Given the development of the RNA deep-sequencing technology and the improvement of algorithms, some CircRNAs are discovered to encode proteins through the cap-independent mechanism and participate in the important process of tumorigenesis and development. Based on an overview of CircRNAs, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 136 publications
(139 reference statements)
0
45
0
Order By: Relevance
“…Adding poly(A) tails lowers mRNA immunogenicity by lowering U content and shielding mRNA in the sequence. The reduced efficacy of protein expression produced by high GC concentration needs to be addressed (Wang et al 2021 ). mRNA purification is also required after IVT to eliminate immunogenicity.…”
Section: Eliminating Mrna Immunogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Adding poly(A) tails lowers mRNA immunogenicity by lowering U content and shielding mRNA in the sequence. The reduced efficacy of protein expression produced by high GC concentration needs to be addressed (Wang et al 2021 ). mRNA purification is also required after IVT to eliminate immunogenicity.…”
Section: Eliminating Mrna Immunogenicitymentioning
confidence: 99%
“…Most vaccines are derived from antiviral immunity (Rabinovich et al 1994 ). At present, various virus-specific vaccines are administered for routine vaccination, resulting in substantial advancements in the prevention and treatment of viral illnesses (Wang et al 2021 ). The first report of the successful use of in vitro transcribed (IVT) mRNA in animals was reported in 1990 (Pardi et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally circRNAs cannot be flipped, but with deeper research, it was found that exon sequences of some circRNAs can be translated into proteins ( Chen and Shan, 2021 ; Dodbele et al, 2021 ). Some circRNAs contain internal ribosome entry site (IRES) sequences and can bind directly to ribosomes and can be translated in eukaryotic cells ( Abe et al, 2015 ; He L. et al, 2021 ). The 40S subunit of eukaryotic ribosomes binds to circRNAs and can directly initiate translation ( Wang and Wang, 2015 ).…”
Section: Biological Functions Of Circular Rnasmentioning
confidence: 99%
“…Notably, circRNA could also translate proteins through rolling circle amplification (RCA) mechanism. To be specifically, the number of nucleotide of these circRNAs is multiple of three and they only have start codons but lack of stop codons, which theoretically means high-molecular weight proteins could be produced once translation begins ( 106 ) ( Figure 2D ).…”
Section: An Overview Of Circrnamentioning
confidence: 99%